On the Possibility of Forming a Corium Pool by Induction Heating in a Melt Trap of the Lava-B Facility; Applied Sciences; Vol. 13, iss. 4 - Skakov M. Mazhyn; Baklanov V. Viktor; Akaev A. Assan; Kukushkin I. Ivan; Bekmuldin M. Maxat; Toleubekov K. Kuanyshbek; Gradoboev A. V. Aleksandr Vasilyevich; Stepanova S. Olga (2023, 2023)
Title screen